A new evolutionary distance of amino acid sequences and its application - XIE Xiao-li; LIANG Li-ping; DU Jun-li; YUAN Zhi-fa (浙江大学学报. 农业与生命科学版)
Under the theme of selection, the dynamic equation of amino acid sequences was built, and a new evolution distance (selection evolution distance) was proposed. The new evolution distance's properties were analyzed, and it contained other distances of protein sequence. The dynamic equation could be transformed into a linear regression model, then the parameter b was estimated by the least square method. The amino acid sequences of cytochrome b in 17 species were taken as an example to illustrate the new evolution distance, and the different evolution trees based on different evolution distances were compared by the bootstrap. The results showed that the topology of the evolution tree based on selection evolution distance was consistent with that based on other distances. The new distance provide a new method to estimate evolution distance of amino acid sequences.